Method for improving interfacial strength of porous PEEK composite material
By introducing polyvinylpyrrolene and foaming technology into porous PEEK composites, the problem of insufficient interfacial strength is solved, the mechanical properties and durability of the material are significantly improved, the cost is reduced, and the preparation process is simplified.
Patent Information
- Application Number
- CN202411276216.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2025-01-03
AI Technical Summary
The interface strength of existing porous PEEK composite materials is insufficient, resulting in problems such as stress concentration, interface debonding and crack propagation, affecting its mechanical properties and durability.
By mixing PLA with PCL and introducing water-soluble polymer polyvinylpyrrolene (PVP), mixing uniformly under high shear force, and dispersing uniformly with PEEK through a melt mixer, combining foaming technology to form a uniform pore structure, and finally Soak in serum to improve biocompatibility.
The interface bonding force between PLA, PCL and PEEK matrix is significantly improved, the overall mechanical properties and durability of the composite material are enhanced, the cost is reduced, and the preparation process is simplified.
Smart Images

Figure CN119241898A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of medical devices, and in particular to a method for improving the interface strength of a porous PEEK composite material. Background Art
[0002] In the precision manufacturing and innovative development of medical devices, the selection and application of materials directly determine the performance, safety and service life of the products. With the continuous advancement of materials science, polymer composites have become an important direction for material innovation in the field of medical devices due to their unique advantages: design flexibility, performance adjustability and relative cost-effectiveness. This type of composite material uses design strategies to organically combine polymers with different functional properties such as polylactic acid (PLA), polycaprolactone (PCL) and polyetheretherketone (PEEK), aiming to create a comprehensive performance system that exceeds the performance limitations of a single material.
[0003] PLA, as a representative of green biomaterials, is an ideal choice for applications such as medical implants, sutures and degradable packaging materials due to its biodegradability and excellent biocompatibility. However, PLA's mechanical strength is insufficient, especially under high load or complex stress environments, making it difficult to meet the strict requirements of medical devices for material strength.
[0004] PCL shows great potential in the field of drug controlled release and tissue engineering due to its excellent flexibility and processing properties; its good stress dispersion ability helps to reduce the pressure of the implant on the surrounding tissue, but the limitations of mechanical strength restrict its use in applications that require high-strength support structures.
[0005] PEEK, as a model of high-performance engineering plastics, has excellent mechanical strength, chemical corrosion resistance and biological inertness, making it an indispensable material for manufacturing high-end medical devices such as orthopedic implants and surgical instruments; however, the high cost and processing difficulty limit the widespread application of PEEK, especially in cost-sensitive medical devices and large-scale production.
[0006] In order to overcome the limitations of these single materials, it is particularly important to develop composite materials based on PLA, PCL and PEEK; however, the key challenge of composite materials is how to effectively enhance the interface strength between different polymer matrices; the interface is the key area for the transmission of composite material properties, and its insufficient strength will lead to problems such as stress concentration, interface debonding and crack propagation, which will seriously affect the overall mechanical properties and durability of the composite material.
[0007] Therefore, it is necessary to provide a method for improving the interface strength of porous PEEK composite materials to solve the above technical problems. Summary of the invention
[0008] The invention overcomes the shortcomings of the prior art and provides a method for improving the interface strength of a porous PEEK composite material.
[0009] To achieve the above object, the technical solution adopted by the present invention is: a method for improving the interface strength of a porous PEEK composite material, comprising the following steps:
[0010] S1: PLA and PCL are mixed to form a first mixture, and the mixture is uniformly mixed by high shear force using a twin-screw extruder;
[0011] S2: gradually adding the preheated water-soluble polymer powder to the first mixture, continuing high shear mixing to form a second mixture, maintaining the temperature close to S1 to prevent polymer failure;
[0012] S3: molten PEEK is mixed with the second mixture to form a composite material, and mixed by a melt mixer to ensure uniform dispersion;
[0013] S4: using a foaming agent to foam the composite material to form a desired pore structure;
[0014] S5: soaking the foamed composite material in a solvent to remove the water-soluble polymer, and then drying the soaked composite material to prevent deformation of the material;
[0015] S6: The composite material is soaked in serum to ensure full penetration; it is then dried again to remove excess water.
[0016] In a preferred embodiment of the present invention, in S1, the mass ratio of PLA to PCL is in the range of 1-2:2-4, the mixing temperature is in the range of 150-160°C, and the mixing time is in the range of 10-15 min.
[0017] In a preferred embodiment of the present invention, in S2, the mass ratio of the water-soluble polymer powder to the first mixture is in the range of 1-8:1-12, and the mixing time is in the range of 15-20 min.
[0018] In a preferred embodiment of the present invention, in S2, the water-soluble polymer is polyvinyl pyrrolidone (PVP).
[0019] In a preferred embodiment of the present invention, in S3, the operating temperature of the melt mixer is in the range of 300-400° C., and the mixing time is in the range of 15-30 min.
[0020] In a preferred embodiment of the present invention, in S3, the mass ratio of PEEK to the second mixture is in the range of 1-5:5-10.
[0021] In a preferred embodiment of the present invention, in S4, the foaming agent is carbon dioxide.
[0022] In a preferred embodiment of the present invention, in S4, the foaming temperature ranges from 180 to 200° C., the foaming pressure ranges from 5 to 10 MPa, and the foaming time ranges from 5 to 15 min.
[0023] In a preferred embodiment of the present invention, in S5, the soaking time of the foamed composite material is in the range of 10-20 hours, the drying temperature is in the range of 60-80° C., and the drying time is in the range of 12-24 hours.
[0024] In a preferred embodiment of the present invention, in S6, the composite material is immersed in serum for a time range of 20-30 hours, and the drying temperature range is 60-80°C.
[0025] The present invention solves the defects existing in the background technology and has the following beneficial effects:
[0026] (1) The present invention provides a method for improving the interfacial strength of a porous PEEK composite material. The method introduces a water-soluble polymer, polyvinyl pyrrolidone, as a compatibilizer, which plays a bridging role in the mixing process of PLA, PCL and PEEK, effectively promoting the interaction and entanglement between different polymer molecular chains. The compatibilization effect significantly improves the interfacial bonding force between PLA, PCL and PEEK matrix, so that when the composite material is subjected to external force, it is not easy to debond or be damaged at the interface, thereby greatly improving the overall mechanical properties and durability of the composite material. In addition, the uniform pore structure formed during the foaming process further enhances the interfacial bonding of the material, provides additional mechanical support points for the composite material, and further optimizes the interfacial strength.
[0027] (2) The present invention ensures that PLA, PCL and PEEK can be fully fused during the melt mixing process to form a uniform composite material system by controlling the process parameters of each step, such as mixing temperature, time and the amount of water-soluble polymer added. In particular, the use of water-soluble polymers not only improves the compatibility between polymers, but also promotes the diffusion and entanglement of molecular chains at the interface, reduces interface defects, and improves the density and continuity of the interface area. The optimization of interface compatibility directly leads to a significant improvement in the interface strength of the composite material, so that the composite material can exhibit excellent performance stability in a variety of application scenarios.
[0028] (3) Compared with directly using PEEK materials, the present invention prepares a porous structure by reasonably mixing PLA, PCL and PEEK and combining foaming technology, thereby effectively reducing the overall cost of the composite material. In addition, the use of mature processes such as twin-screw extruders and melt mixers for mixing and molding not only simplifies the preparation process but also improves production efficiency. At the same time, the consistency and stability of the composite material are ensured by precisely controlling the process parameters of each step, such as temperature, time and pressure. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art are briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative work.
[0030] Figure 1 It is a flow chart of a preferred embodiment of the present invention. DETAILED DESCRIPTION
[0031] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention can also be implemented in other ways different from those described herein. Therefore, the protection scope of the present invention is not limited to the specific embodiments disclosed below.
[0033] like Figure 1 As shown, the present invention provides a method for improving the interface strength of porous PEEK composite materials:
[0034] S1: PLA and PCL are mixed to form a first mixture, and the mixture is uniformly mixed by high shear force using a twin-screw extruder.
[0035] S2: Gradually add the preheated water-soluble polymer powder to the first mixture, continue high shear mixing, and form a second mixture, keeping the temperature close to S1 to prevent polymer failure.
[0036] S3: The molten PEEK is mixed with the second mixture to form a composite material, and mixed by a melt mixer to ensure uniform dispersion.
[0037] S4: Using a foaming agent to foam the composite material to form a desired pore structure.
[0038] S5: soaking the foamed composite material in a solvent to remove the water-soluble polymer, and then drying the soaked composite material to prevent deformation of the material.
[0039] S6: The composite material is soaked in serum to ensure full penetration; it is then dried again to remove excess water.
[0040] In S1, the mass ratio of PLA to PCL is in the range of 1-2:2-4, the mixing temperature is in the range of 150-160°C, and the mixing time is in the range of 10-15 min.
[0041] In S2, the mass ratio of the water-soluble polymer powder to the first mixture is in the range of 1-8:1-12, the mixing time is in the range of 15-20 min, and the water-soluble polymer is: polyvinyl pyrrolidone (PVP);
[0042] In S3, the operating temperature range of the melt mixer is 300-400° C., the mixing time range is 15-30 min, and the mass ratio of PEEK to the second mixture ranges from 1-5:5-10;
[0043] In S4, the foaming agent is carbon dioxide, the foaming temperature ranges from 180 to 200°C, the foaming pressure ranges from 5 to 10 MPa, and the foaming time ranges from 5 to 15 min;
[0044] In S5, the foamed composite material is immersed for a time range of 10-20 hours, dried at a temperature range of 60-80°C, and dried for a time range of 12-24 hours;
[0045] In S6, the composite material is immersed in serum for a time ranging from 20 to 30 h, and the drying temperature ranges from 60 to 80°C.
[0046] It should be noted that: first, polylactic acid (PLA) and polycaprolactone (PCL) are uniformly mixed in a temperature range of 150-160°C for 10-15 minutes through the high shear force of a twin-screw extruder to form a first mixture. This process not only ensures the full mixing of the two polymers at the molecular level and improves the overall performance of the composite material, but also promotes the compatibility between PLA and PCL through physical mixing, laying a good foundation for subsequent steps.
[0047] Subsequently, the preheated water-soluble polymer powder (such as polyvinyl pyrrolidone PVP) is gradually added to the first mixture, and high shear mixing is continued to form a second mixture. The temperature is kept close to S1 to prevent polymer failure. PVP, as a compatibilizer, effectively promotes the compatibility between PLA, PCL and the subsequently added PEEK, while ensuring the uniform dispersion of PVP powder in the second mixture.
[0048] Next, the molten PEEK is mixed with the second mixture, and the PEEK and the second mixture are uniformly compounded by a melt mixer at a high temperature of 300-400°C and under high shear force. This step significantly enhances the mechanical properties, heat resistance and chemical resistance of the composite material, and by precisely controlling the mass ratio of PEEK to the second mixture, the material performance requirements of different applications are met.
[0049] Afterwards, the composite material is foamed and molded using a foaming agent. By adjusting parameters such as the amount of foaming agent, foaming temperature and pressure, the size, shape and distribution of the pores are precisely controlled, achieving a lightweight design of the composite material and possibly improving its water absorption, air permeability and biocompatibility.
[0050] The foamed composite material needs to be soaked in solvent to remove water-soluble polymers (such as PVP), and then dried to prevent the material from deforming. This step effectively removes impurities in the composite material, improves the purity of the material, and ensures its shape stability.
[0051] Finally, the composite material is soaked in serum to ensure full penetration, so that the proteins and other biomolecules in the serum are adsorbed on the surface of the material, promoting cell attachment and growth, thereby improving the biocompatibility of the composite material. The soaked composite material needs to be dried again to remove excess water to ensure its stability and durability.
[0052] Embodiment 1:
[0053] S1: PLA and PCL are mixed to form a first mixture, and the mixture is uniformly mixed by a twin-screw extruder through high shear force, the mass ratio of PLA to PCL is 1:2, the mixing temperature is 155°C, and the mixing time range is 13 minutes;
[0054] S2: gradually add the preheated polyvinyl pyrrolidone (PVP) powder to the first mixture, continue high shear mixing to form a second mixture, keep the temperature the same as S1 to prevent polymer failure. The mass ratio of polyvinyl pyrrolidone (PVP) to the first mixture is 4:6, and the mixing time is 17 minutes;
[0055] S3: molten PEEK is mixed with the second mixture to form a composite material, and mixed by a melt mixer to ensure uniform dispersion. The operating temperature of the melt mixer is 350° C., the mixing time is 17 min, and the mass ratio of PEEK to the second mixture is 2-8;
[0056] S4: using a foaming agent to foam the composite material to form a desired pore structure, the foaming agent is carbon dioxide, the foaming temperature is 190° C., the foaming pressure is 7 MPa, and the foaming time is 10 min;
[0057] S5: soaking the foamed composite material in a solvent to remove polyvinyl pyrrolidone (PVP), and then drying the soaked composite material to prevent deformation of the material. The foamed composite material is soaked for 15 hours, the drying temperature is 70° C., and the drying time is 20 hours;
[0058] S6: The composite material is immersed in serum to ensure sufficient penetration; then it is dried again to remove excess moisture. The composite material is immersed in serum for 25 hours and the drying temperature is below 70°C.
[0059] Comparative Example 1:
[0060] S1: PLA and PCL are mixed to form a first mixture, and the mixture is uniformly mixed by a twin-screw extruder through high shear force, the mass ratio of PLA to PCL is 1:2, the mixing temperature is 155°C, and the mixing time range is 13 minutes;
[0061] S2: molten PEEK is mixed with the first mixture to form a composite material, and mixed by a melt mixer to ensure uniform dispersion. The operating temperature of the melt mixer is 350° C., the mixing time is 17 min, and the mass ratio of PEEK to the second mixture is 2-8;
[0062] S3: Soak the composite material in serum to ensure sufficient penetration; then dry it again to remove excess moisture. The composite material is soaked in serum for 25 hours and the drying temperature is 70°C.
[0063] Comparative Example 2:
[0064] S1: PLA and PCL are mixed to form a first mixture, and the mixture is uniformly mixed by a twin-screw extruder through high shear force, the mass ratio of PLA to PCL is 1:2, the mixing temperature is 155°C, and the mixing time range is 13 minutes;
[0065] S2: gradually add the preheated polyvinyl pyrrolidone (PVP) powder to the first mixture, continue high shear mixing to form a second mixture, keep the temperature the same as S1 to prevent polymer failure. The mass ratio of polyvinyl pyrrolidone (PVP) to the first mixture is 4:6, and the mixing time is 17 minutes;
[0066] S3: The molten PEEK is mixed with the second mixture to form a composite material, and mixed by a melt mixer to ensure uniform dispersion. The operating temperature of the melt mixer is 350° C., the mixing time is 17 min, and the mass ratio of PEEK to the second mixture is 2-8.
[0067] S4: soaking the composite material in a solvent to remove polyvinyl pyrrolidone (PVP), and then drying the soaked composite material to prevent deformation of the material. The foamed composite material is soaked for 15 hours, dried at 70° C., and dried for 20 hours;
[0068] S5: The composite material is immersed in serum to ensure sufficient penetration; then it is dried again to remove excess moisture. The composite material is immersed in serum for 25 hours and the drying temperature is below 70°C.
[0069] Comparative Example 3:
[0070] S1: PLA and PCL are mixed to form a first mixture, and the mixture is uniformly mixed by a twin-screw extruder through high shear force, the mass ratio of PLA to PCL is 1:2, the mixing temperature is 155°C, and the mixing time range is 13 minutes;
[0071] S2: molten PEEK is mixed with the first mixture to form a composite material, and mixed by a melt mixer to ensure uniform dispersion. The operating temperature of the melt mixer is 350° C., the mixing time is 17 min, and the mass ratio of PEEK to the second mixture is 2-8;
[0072] S3: using a foaming agent to foam the composite material to form a desired pore structure, the foaming agent is carbon dioxide, the foaming temperature is 190° C., the foaming pressure is 7 MPa, and the foaming time is 10 min;
[0073] S4: soaking the foamed composite material in a solvent to remove polyvinyl pyrrolidone (PVP), and then drying the soaked composite material to prevent deformation of the material. The foamed composite material is soaked for 15 hours, the drying temperature is 70° C., and the drying time is 20 hours;
[0074] S5: The composite material is immersed in serum to ensure sufficient penetration; then it is dried again to remove excess moisture. The composite material is immersed in serum for 25 hours and the drying temperature is 70°C.
[0075] experiment:
[0076] Sample preparation: The composite sample was processed into a dumbbell-shaped tensile test shape, ensuring that the interface was located in the middle of the sample;
[0077] Test equipment: Use universal testing machine tensile test equipment for testing;
[0078] Test process: Install the sample on the testing machine and stretch it at a constant speed until the sample breaks. Record the maximum force at break and the cross-sectional area of the sample;
[0079] Interface strength calculation: Interface strength can be calculated by the following formula:
[0080] Table 1:
[0081]
[0082]
[0083] From Table 1 we can see that:
[0084] Example 1: The addition of PVP and the foaming process are combined, and a composite material with a uniform pore structure is finally obtained through multi-step mixing and foaming molding.
[0085] Comparative Example 1: No PVP was added and no foaming treatment was performed, and the composite material was prepared only by melt mixing.
[0086] Comparative Example 2: PVP was added but no foaming treatment was performed, and the composite material was obtained after the PVP was removed by a solvent.
[0087] Comparative Example 3: PVP was not added but foaming treatment was performed, and a composite material was obtained after foaming molding.
[0088] Experimental results and analysis
[0089] Interface strength calculation:
[0090] According to the experimental data, the interfacial strength (MPa) of each group of samples is calculated in Table 1. Using the formula The maximum force at break (N), the cross-sectional area of the specimen (mm 2 ).
[0091] The interface strength of Example 1 is 23.94 MPa.
[0092] The interface strength of Comparative Example 1 is 17.61 MPa.
[0093] The interface strength of Comparative Example 2 is 19.30 MPa.
[0094] The interface strength of Comparative Example 3 is 15.34 MPa.
[0095] Comparative experimental analysis:
[0096] Addition of PVP: By comparing Example 1 with Comparative Example 1, it can be seen that the addition of PVP significantly improves the interface strength of the composite material (from 17.61 MPa to 23.94 MPa), indicating that PVP plays an important role in enhancing interface bonding.
[0097] Influence of foaming process: By comparing Example 1 with Comparative Example 2, it can be seen that the foaming process also has a certain improvement effect on the interface strength (from 19.30 MPa to 23.94 MPa). Although the improvement is small, it proves that foaming can improve the microstructure of the material, thereby enhancing the interface bonding.
[0098] The combined effect of PVP and foaming: By comparing Example 1 with Comparative Example 3, it can be seen that the combined effect of PVP and the foaming process has the most significant effect on improving the interface strength. Example 1 has the highest interface strength (23.94 MPa), while Comparative Example 3 (foaming only, no PVP added) has the lowest interface strength (15.34 MPa), indicating that the combination of the two can maximize the enhancement of interface bonding.
[0099] SEM observation results:
[0100] The SEM image observation further verifies the results of the mechanical test. The sample of Example 1 has a tight interface and a uniformly distributed pore structure, which is consistent with its high interface strength.
[0101] The sample of Comparative Example 1 has general interface bonding and no porous structure, which explains its lower interface strength.
[0102] Although the interface of the sample in comparative example 2 is tightly bonded, its interface strength is slightly lower than that of example 1 because it is not foamed and lacks a pore structure.
[0103] The sample of comparative example 3 has general interface bonding and a porous structure, which is consistent with its lowest interface strength.
[0104] In summary:
[0105] This experiment compared the interface strength of composite materials under different preparation conditions, proving that both the addition of PVP and the foaming process have a positive effect on the interface strength. Among them, the addition of PVP can significantly improve the interface bonding strength, while the foaming process further enhances the interface bonding by improving the microstructure of the material. When the two work together, the interface strength of the composite material reaches the highest.
[0106] The above is based on the ideal embodiment of the present invention. Through the above description, relevant personnel can make various changes and modifications without departing from the technical concept of the present invention. The technical scope of the present invention is not limited to the content in the specification, and the technical scope must be determined according to the scope of the claims.
Claims
1. A method for improving the interfacial strength of a porous PEEK composite material, characterized in that: The following steps are involved: S1: PLA and PCL are mixed to form a first mixture, and the mixture is uniformly mixed by high shear force using a twin-screw extruder; S2: gradually adding the preheated water-soluble polymer powder to the first mixture, continuing high shear mixing to form a second mixture, maintaining the temperature close to S1 to prevent polymer failure; S3: molten PEEK is mixed with the second mixture to form a composite material, and mixed by a melt mixer to ensure uniform dispersion; S4: using a foaming agent to foam the composite material to form a desired pore structure; S5: soaking the foamed composite material in a solvent to remove the water-soluble polymer, and then drying the soaked composite material to prevent deformation of the material; S6: The composite material is soaked in serum to ensure full penetration; Then dry it again to remove excess water.
2. A method for improving the interfacial strength of a porous PEEK composite material according to claim 1, characterized in that: In the S1, the mass ratio of PLA to PCL is in the range of 1-2:2-4, the mixing temperature is in the range of 150-160° C., and the mixing time is in the range of 10-15 min.
3. A method for improving the interfacial strength of a porous PEEK composite material according to claim 1, characterized in that: In S2, the mass ratio of the water-soluble polymer powder to the first mixture is in the range of 1-8:1-12, and the mixing time is in the range of 15-20 min.
4. The method for improving the interfacial strength of a porous PEEK composite material according to claim 1, characterized in that: In S2, the water-soluble polymer is polyvinyl pyrrolidone (PVP).
5. The method for improving the interfacial strength of a porous PEEK composite material according to claim 1, characterized in that: In S3, the operating temperature of the melt mixer is in the range of 300-400°C, and the mixing time is in the range of 15-30 minutes.
6. The method for improving the interfacial strength of a porous PEEK composite material according to claim 1, characterized in that: In S3, the mass ratio of PEEK to the second mixture is in the range of 1-5:5-10.
7. The method for improving the interfacial strength of a porous PEEK composite material according to claim 1, characterized in that: In S4, the foaming agent is carbon dioxide.
8. The method for improving the interfacial strength of a porous PEEK composite material according to claim 1, characterized in that: In the S4, the foaming temperature ranges from 180 to 200°C, the foaming pressure ranges from 5 to 10 MPa, and the foaming time ranges from 5 to 15 min.
9. The method for improving the interfacial strength of a porous PEEK composite material according to claim 1, characterized in that: In S5, the soaking time of the foamed composite material is in the range of 10-20 hours, the drying temperature is in the range of 60-80° C., and the drying time is in the range of 12-24 hours.
10. The method for improving the interfacial strength of a porous PEEK composite material according to claim 1, characterized in that: In S6, the composite material is immersed in serum for 20-30 hours, and the drying temperature is 60-80°C.
